Specific features of adsorption of azo dyes on fly ash - SARIER, NİHAL (My University, 2007)
A possibility to utilize fly ash (FA) formed at coal-fired power plants as a cheap adsorbent for the purification of wastewater containing azo dyes methylene blue (MB) and methyl red (MR) was considered. The effect of an FA additive on the adsorption capacity of active carbon was studied. The efficiency of FA as an adsorbent for the purification of aqueous solutions from MB and MR was shown. The adsorption is also fairly efficient when active carbon is partially replaced by FA.
Keywords: adsorption; azo dyes; fly ash; X-ray diffraction analysis; wastewater